Individual Factors and Student Involvement in Extra Curricular Activities - Wijewantha, Prabhashini (Gyan Management Journal, 2013)
The study focuses on how individual factors affect students’ involvement in Extra Curricular activities at the university. Primary data are collected through a Questionnaire from 100 undergraduates sel